2012
DOI: 10.1179/204777312x13305103762501
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant screening for TB: a missed opportunity to improve TB control in the United Kingdom

Abstract: Tuberculosis in the United Kingdom and other high-income countries is primarily a disease of the foreignborn arising from the synergy of migration from high TB burden regions and the reactivation of remotely acquired latent TB infection. UK immigrant screening policy primarily aims to identify active, rather than latent, TB although mounting evidence indicates that implementing latent TB screening for new entrants from intermediate and high incidence countries could cost-effectively reduce TB incidence in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…First, it compared the cost-effectiveness of TST and each of the two IGRA platforms for new entrant screening and found that single-step testing is more cost-effective than two-step testing, particularly with QFT-GIT. Second, taken together with a previous new entrant screening study,29 it supports a recently proposed streamlined algorithm to new entrant LTBI screening, reserving chest radiography only for those testing positive by IGRA 25. This emerging approach, however, assumes that IGRA false-negative rates in contacts with asymptomatic active TB are very low, but more data are needed to support this 25.…”
Section: Current and Future Policymentioning
confidence: 73%
See 1 more Smart Citation
“…First, it compared the cost-effectiveness of TST and each of the two IGRA platforms for new entrant screening and found that single-step testing is more cost-effective than two-step testing, particularly with QFT-GIT. Second, taken together with a previous new entrant screening study,29 it supports a recently proposed streamlined algorithm to new entrant LTBI screening, reserving chest radiography only for those testing positive by IGRA 25. This emerging approach, however, assumes that IGRA false-negative rates in contacts with asymptomatic active TB are very low, but more data are needed to support this 25.…”
Section: Current and Future Policymentioning
confidence: 73%
“…Given that >75% of the UK’s TB burden is carried by foreign-born immigrants, and most of this is due to reactivation of LTBI within the first several years after arrival, tackling imported LTBI in new entrants is increasingly recognised as an attractive strategy to reverse the relentless rise in UK TB rates 25. Policy is evolving rapidly in this area in response to a growing evidence base.…”
Section: Current and Future Policymentioning
confidence: 99%
“…Several studies attribute rising TB rates to a combination of an increased number of TB cases and reactivation of latent infection among immigrants in UK. [9][10][11][12] In the USA, the decline in annual TB rates has been attributed to ongoing improvements in TB control practices and a decline in incidence among the foreign-born. 8 [13][14][15] In this study, we examined trends in the number of reported TB cases and incidence rates between…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, TB notifications have increased continuously over the past 30 years and of the 9000 new cases notified in 2011, 74% occurred among foreign-born individuals 3. Strategies for the effective control and elimination of TB in low-incidence countries, such as the UK, depend on the prompt identification and management of active disease, and also those individuals with latent TB infection (LTBI) who are at risk of reactivation, progression to disease and infectiousness 4 5…”
Section: Introductionmentioning
confidence: 99%